Size effects in p-PbTe nanostructures on polyamide - Freik, D.M.; Yurchyshyn, I.K.; Potyak, V.Yu.; Lysiuk, Yu.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The thickness dependences of the thermoelectric parameters were observed at
room temperature for nanostructures p-PbTe, grown from the vapor phase on polyamide
film substrates. An attempt to explain detected dependences in the range of quantum
theory was done.